2013
DOI: 10.1104/pp.113.218065
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Complex Regulation of AtALMT1 Expression in Response to Phytohormones and Other Inducers    

Abstract: In Arabidopsis (Arabidopsis thaliana), malate released into the rhizosphere has various roles, such as detoxifying rhizotoxic aluminum (Al) and recruiting beneficial rhizobacteria that induce plant immunity. ALUMINUM-ACTIVATED MALATE TRANSPORTER1 (AtALMT1) is a critical gene in these responses, but its regulatory mechanisms remain unclear. To explore the mechanism of the multiple responses of AtALMT1, we profiled its expression patterns in wild-type plants, in transgenic plants harboring various deleted promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 44 publications
(51 reference statements)
2
64
1
Order By: Relevance
“…Yang et al 2011). The AtALMT1 was also reported to be regulated by phytohormones such as auxin and abscisic acid (Kobayashi et al 2013). Under the circumstances, if Al ions affect auxin distribution at the root apex as suggested previously (Kollmeier et al 2000;Abdalla 2008;Hong et al 2008), Al ions could indirectly control auxininducible genes including SUT1 and ALMT1, and hence inhibit root growth.…”
Section: Ntsut1 Confers Al Tolerancementioning
confidence: 76%
“…Yang et al 2011). The AtALMT1 was also reported to be regulated by phytohormones such as auxin and abscisic acid (Kobayashi et al 2013). Under the circumstances, if Al ions affect auxin distribution at the root apex as suggested previously (Kollmeier et al 2000;Abdalla 2008;Hong et al 2008), Al ions could indirectly control auxininducible genes including SUT1 and ALMT1, and hence inhibit root growth.…”
Section: Ntsut1 Confers Al Tolerancementioning
confidence: 76%
“…7). While it remains to be investigated whether our transgenic tobacco plants are also resistant to the attack of bacterial pathogens, the expression of Arabidopsis for Aluminum-activated Malate Transporter1 has been documented to be involved in both Al tolerance and pathogen resistance (Rudrappa et al, 2008;Lakshmanan et al, 2012;Kobayashi et al, 2013). In our previous study, a pathogenesis-related gene was found to be up-regulated by Al stress in rice bean .…”
Section: Discussionmentioning
confidence: 89%
“…The complex transcriptional regulation of these orthologs is consistent with the pleiotropic roles of the root-excreted malate. Transcription of the Arabidopsis ortholog AtALMT1 is activated by Al and by other signal inducers, including a type of microbe-associated molecular pattern peptide, flagellin22 (Kobayashi et al, 2013a). GmALMT1 expression is induced by multiple stressors, namely Al, phosphorus deficiency, and low pH (Liang et al, 2013).…”
mentioning
confidence: 99%
“…promoter function (Kobayashi et al, 2013a). In addition, several bioinformatic procedures have been developed to predict cis-elements (Tompa et al, 2005;Zou et al, 2011).…”
mentioning
confidence: 99%